The legal entity : the influence of the accounting expert reports in the judicial decisions on disregard doctrine according to the Communicative Action Theory - INOCÊNCIO JUNIOR, João (2022)
The dissertation aimed to analyze the accounting principle of legal entities on the rule of judicial decision in civil law cases that uses accounting information as evidence in judicial decisions (RQ1) about the disregard of legal personality (doctrine of disregard) using the Theory of Communicative Action by Habermas with an emphasis on how judges are influenced by expert reports (RQ2). Trough Content Analyses with the use of non-parametrical statistics to measure the effectiveness of the communication, we collected data from real cases, cataloged, classified in order to check 4 hypotheses. In my results the first hypothesis (H1) which measures the sole presence of characteristics in the Report could influence the occurrence of disregard with all the sample it’s found that despite respecting the accounting regulation, the reports did not improve the communicative process. The second hypothesis (H2) that analyzes whether the value on litigation influences the judge to consider the content of the Expert Evidence Reports on his Decision. That hypothesis is confirmed is also valid to mention that few judges consider the report in their judgments. The third hypothesis (H3) deals with the matter of approach of the language used (normative versus positivist) that Hypothesis confirms that the experts use technicism (positivist language). The H4 (which makes a correlation between the well informed report and the influence) is confirmed and when the reports shows more non-mandatory characteristics indicates when the accountants are more communicative their role in the judicial lawsuits they have their reports more considered in their role as Experts. This research found some limitations: law secrecy of accounting books and lawsuits with legal sigil. Another limitations were the lack inclusion of reverse disregard due to the lack of time; For further research considering that the critical researchers tend to seeks answers in neuroscience and through the critical assessment of speech to understand the actors in the communicative processes then, is recommended (in a doctoral thesis) for a more useful use of the collected data that the appointed judicial expert reports (laudos periciais) and with the Judicial Decision can be analyzed with the criteria of Critical Theory in a analysis of content. With the aim of knowing the meaning of reality and praxis. It is also recommended the use of interviews and surveys: with judges and with accounting professionals in order to know their professional abilities and perspectives in order to improve this study on the communicative process. Another perspective may use the Foucauldian Decision Theory with emphasis on the power relations.